The Strange Case of Dr. Jekyll and Mr. Hyde. - Stevenson, Robert Louis (Open Road Media, 2014)
The most infamous of horror stories-a disturbing examination of man's capacity for evilOne pitch-black London morning, a ghoulish little man tramples a young girl and continues heedlessly on his way. Caught by a passerby and returned to the scene of the crime, the man is forced to pay £100 in restitution. He produces ten pounds in gold and a check for the remainder. Curiously, the check bears the signature of the well-regarded Dr. Henry Jekyll. Even stranger, Dr. Jekyll's will names this same awful and mysterious little man, Mr. Hyde, as the sole beneficiary. Troubled by the coincidence, Dr. J.